CD4+IL9+ (Th9) cells as the major source of IL-9, potentially modulate Th17/Treg mediated host immune response during experimental cerebral malaria. (December 2022) - Ghosh, Soubhik; Mukherjee, Saikat; Sengupta, Anirban; Chowdhury, Sreyoshi; Sarkar, Samrat; Keswani, Tarun; Bhattacharyya, Arindam
Abstract: Th9, a new subgroup of CD4 + T cells is characterized by its specific cytokine IL-9, is a critical factor in allergic diseases, cancers and parasitic infections. This study aimed to explore the potential roles of Th9 cells in the immunopathogenesis of ECM. In splenocytes sourced from uninfected, Pb A and Py infected mice, Th9 cells were characterised by flow cytometry, cell sorting and qPCR. Enhancement of CD4 + IL-9 + (Th9) cells were observed in both the infections, which corroborated with increased expression of the differentiating transcription factors. Moreover, crucial cytokine receptors (IL-4R, TGF-βR, IL-6R) as well as chemokine receptors (CCR3, CCR6 and CCR7) and activation marker (CD96), demonstrated elevation upon PbA infection in splenic Th9 cells. Furthermore, Neutralization of IL-9 along with IL-6 enhanced host survivability, reduced mean neurological score of ECM. However, anti- IL-9 treatment also down regulated frequency of Th17 cells, and its transcription factors pSTAT3, RORγT along with depleted Il-1β and Il-6 expression . In sum, understanding how IL-9 producing CD4 + T-cells can alter Th17/Treg ratio and by that modulate host's immune response, could pave the way for developing immunomodulatory interventions against cerebral malaria. Graphical Abstract: ga1 Highlights: Increased frequency of CD4 + IL9 + cells (Th9) in peripheral circulation and spleen upon Pb A and P.yoelii infection. Elevated expression of CD96 and IL-6R observed on splenic Th9 cells during Pb A infection. Neutralization of IL-9 increased survivability and decrease disease severity during experimental cerebral malaria (ECM). Anti-IL-9 treatment modulated Th17/Treg mediated immune balance and dampened aggressive pro-inflammatory immune response.